Linguistic interference and bilingualism: exploring code-switching, language shift and the role of metaphors in cross-linguistic communication - al-Saadi, Salim Nasser (Journal of the Belarusian State University. Philology, 2025)
The article analyses aspects of the language contact theory and the phenomenon of bilingualism. The influence of linguistic interference on bilinguals and cross-cultural communication is discussed. The patterns of code-switching, language shift and language convergence are studied, and psychological and social factors of bilingual interaction are examined. Interference is considered at the phonological, grammatical and lexical levels. The role of metaphors in cross-linguistic communication, in particular in political discourse, is determined. The results of the study can contribute to the implementation of communication in heterogeneous conditions.